Manner Affixes and Event Decomposition - Victor Bogren Svensson (Languages)
This paper investigates how verbal affixes that encode manner information (manner affixes) interact with verbs of different lexical aspect classes and transitivity values in West Greenlandic (Inuit–Yupik–Unangan: Greenland). Manner affixes remain an understudied and poorly understood grammatical category. The data presented and discussed here is primarily based on original fieldwork conducted in Copenhagen (Denmark) and Nuuk (Greenland). The findings show that manner affixes are interspersed among syntactic projections encoding event and argument structure, with a high degree of flexibility in terms of linear and hierarchical ordering, which correlate with differences in scope interpretation. However, this flexibility is limited by the productivity of the affixes involved, and manner affixes cannot intervene between the syntactic projections that encode the event core (the big VP in traditional generative terminology). Furthermore, manner affixes interact with verbs of different lexical aspect classes in ways similar to manner adverbs, highlighting the similarities between the two categories and the similarities between morphological structures (manner affixes) and syntactic structures (manner adverbs).